Book presence in a digital age - Brillenburg Wurth, Kiene; Driscoll, Kári; Pressman, Jessica (Bloomsbury Academic, 2018)
"Starting from this idea of media plurality, Book Presence in a Digital Age explores the resilience of print literatures, book art, and zines in the late age of print. It does so within both a contemporary and a historical perspective: even as it focuses on the materiality of books as literary writing in the present, it considers these present developments in the light of earlier "moments" of media transition: from the invention of the printing press to the gramophone, radio, and the movies, the future of the book has been called into question since the early modern era. Bringing together leading scholars, artists, and publishers, Book Presence in a Digital Age offers a variety of perspectives on the past, present, and future of the book as medium, the complex relationship of materiality to virtuality, and of the analog to the digital"--